Current guidelines review for the preservation of plastics emitters of gaseous pollutants in Contemporary Art museums - Liébana Molina, Sara (Ge-conservacion, 2017)
Plastic contemporary artworks preservation is being a research object for the latter years. Even though so, gaseous pollutants emissions problem has not been studied in depth from the conservation-preservation field. This article shows the results after the review on the most recent researches related to this problem. We also include the conclusions from the nineteen answers obtained from the surveys carried out in museums and institutions whose collections hold plastic made objects and pieces of art. The data collection analysis brings to light the absence of specific protocols for plastic preservation, even more so if it is about those emitting gaseous pollutants.